Insights into early generation synthetic amphidiploid Brassica juncea: a strategy to harness maximum parental genomic diversity for improving Indian mustard - Garg, Pooja; Tripathi, Shikha; Kashyap, Anamika; Anil Kumar, A.; Kumari, Sujata; Singh, Mandeep; Kushwaha, Ranjeet; Sharma, Shiv Shankar; Sharma, Jyoti; Yadav, Rashmi; Gupta, N. C.; Singh, Naveen; et al. (Frontiers in Plant Science, 2025)
In India, amphidiploid Brassica juncea (AABB, 2n=36) is a significant oilseed crop, but its small gene pool limits its ability to develop traits of higher breeding and economic value. Through interspecific hybridization from various lines of the progenitor species, resynthesized B. juncea (RBJ) can provide breeders with additional resources for creating genetically diverse stress-tolerant and high-yielding cultivars. Three B. rapa accessions and eight B. nigra accessions were crossed in this study to develop 33 synthetic B. juncea lines. A total of 28 crosses were attempted, including the three-way crosses, but only the cross combinations with B. rapa cytoplasm led to successful embryonic development. Molecular diversity analysis of these lines in S2 generation revealed significant genetic diversity with higher levels of heterozygosity and allelic richness, along with significant variations for the yield-related traits. These results suggest that the synthesized lines could effectively enrich the genetic base of B. juncea and generate variability for agronomically important traits in a shorter time duration. The characterized variability in the synthetic lines needs to be utilized in hybridization, with already evolved genotypes, in early generations before it is lost due to chromosomal rearrangements, recombination and natural selection.